Spin effects in oxygen electrocatalysis: a discussion - Nazmutdinov, Renat R. (2013)
The reduction of molecular oxygen in triplet and singlet spin states at metal electrodes is analyzed in the framework of quantum mechanical theory of charge transfer. Both outer- and inner-sphere mechanism is considered. Singlet oxygen is argued to be considerably more active in electron transfer processes. It is demonstrated that spin polarization may play a catalytic role, parallel with the effect of overlap of reactant orbitals with the d-band of a metal electrode. Our model is based on two main assumptions: (i) some metal surfaces favor the existence of singlet molecular oxygen in adsorbed state; and (ii) short-living singlet O2 molecules may appear as intermediates at some reduction steps. These two reasons are expected to increase the local concentration of active singlet molecular oxygen in reaction layer.